Contingent Employment and Labour Market Pathways: Bridge or Trap? - Duncan McVicar; Mark Wooden; Yin King Fok (Institute of Labor Economics (IZA), 2017)
The debate over whether contingent (and typically more precarious) employment acts as a bridge to permanent employment, or as a trap, has tended to focus on transitions rather than longer-run pathways. This approach cannot accurately identify indirect pathways from contingent to permanent employment, and nor can it identify 'trap' pathways involving short spells in other states. It also fails to distinguish between those experiencing contingent employment as a 'blip' and those with longer spells. This article employs a different approach involving sequence analysis. Exploiting longitudinal data for Australian, evidence for the co-existence of pathways that correspond to 'bridge' and 'trap' characterisations of contingent employment is found. Further, in the case of casual employment these two types of labour market pathways are roughly equally prevalent, although for some groups in particular women, those with low educational attainment, and those with a disability 'traps' are more likely than 'bridges'.
Keywords: J41; C38; 330; casual employment; contingent employment; temporary employment; pathways; segmented labour markets; sequence analysis